Telegram sebagai Media Pemasaran di Era Pandemi - Rafii Muhammad Ris Zikrullah; Oji Kurniadi (Jurnal Riset Public Relations, 2023)
Abstract. The use of Telegram social media as a Marketing Media in the Pandemic Era was chosen by PT. Indonesia Smart Services (LCI) because social media is considered effective to use with some of the features it has. This study aims to find out the reasons for using telegrams in the marketing media of PT. Smart Indonesia Services, the role of telegram as a digital marketing tool for PT. Smart Indonesia Services, and the use of telegrams in the concept of social media ROI at PT. Indonesian Smart Services. This study uses a qualitative method with a case study approach and a constructivist paradigm. Researchers use the theoretical perspective of Social Media ROI (Return of Investment) in discussing this research. Researchers also use the perspective of digital marketing communication theory and new media theory in this study. This research was conducted in the city of Bandung, precisely at the head office of PT. Indonesia Smart Services which is located on Jl. Sadang Sari I, Sekeloa, Coblong since May 2022. The results of this study are: (1) PT. Indonesia Smart Services has three reasons for using telegram as its marketing medium, namely productive age users, low investment, and effectiveness, (2) PT. The Smart Indonesia service uses the telegram feature to share photos, videos, files, group and supergroup features, channel features on telegram with posters, pamphlets, advertisements and videos that are marketed 4-2 weeks before the event takes place. (3) the use of telegrams in the concept of social media ROI is very effective. Abstrak. Pengggunaan media sosial Telegram sebagai Media Pemasaran di Era Pandemi ini dipilih PT. Layanan Cerdas Indonesia (LCI) oleh sebab media sosial tersebut dinilai efektif untuk digunakan dengan beberapa fitur yang dimilikinya. Penelitian ini bertujuan untuk mengetahui alasan penggunaan telegram pada media pemasaran PT. Layanan Cerdas Indonesia, peran telegram sebagai alat pemasaran digital PT. Layanan Cerdas Indonesia, dan penggunaan telegram dalam konsep social media ROI pada PT. Layanan Cerdas Indonesia. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus serta paradigma konstruktivis. Peneliti menggunakan perspektif teori Social Media ROI (Return of Investment) dalam membahas penelitian ini. Peneliti juga menggunakan perspektif teori komunikasi pemasaran digital serta teori media baru dalam penelitian ini. Penelitian ini dilakukan di Kota Bandung, tepatnya di kantor pusat PT. Layanan Cerdas Indonesia yang berlokasi di Jl. Sadang Sari I, Sekeloa, Coblong sejak bulan Mei 2022. Hasil dari penelitian ini adalah : (1) PT. Layanan Cerdas Indonesia memiliki tiga alasan dalam menggunakan telegram sebagai media pemasarannya, yakni pengguna berusia produktif, low investment, dan efektifitas, (2)PT. Layanan Cerdas Indonesia menggunakan fitur telegram berbagi foto, video, file, fitur grup dan supergrup, fitur channel pada telegram dengan isi konten poster, pamphlet, iklan, dan video yang dipasarkan 4-2 minggu sebelum kegiatan berlangsung. (3) penggunaan telegram dalam konsep media social ROI sangat efektif.